PENGARUH PEMBELAJARAN BERBASIS PERMAINAN BERBANTU PERMAINAN KARTU AKUNTANSI TERHADAP KETERAMPILAN BERPIKIR KREATIF - Safirah, Dina; Sumaryati, Sri (JURNAL EDUCATION AND DEVELOPMENT, 2025)
The research was motivated by the problem of creative thinking skills that are not optimal and due to the lack of utilization of various types of learning media. This study aims to examine the effect of game-based learning assisted by accounting card games on creative thinking skills. This research uses a quantitative experimental with a non-equivalent control group pseudo-experimental design. Data collection uses pre-test and post-test of bank reconciliation material that has been adjusted to the indicators of creative thinking skills. Normality test and homogeneity test were used to fulfill the prerequisite test. Hypothesis testing includes Independent Sample t-test, Paired Sample t-test, and N-Gain using SPSS version 26. The results showed that there was an effect of game-based learning assisted by accounting card games on creative thinking skills. This is evidenced by the results of the Independent Sample t-test and Paired Sample t-test tests which show a significance value <0.05 and the N Gain score which shows that there is an increase in creative thinking skills in the moderate category while the control class is in the low category.